2012
DOI: 10.1523/jneurosci.4371-11.2012
|View full text |Cite
|
Sign up to set email alerts
|

Higher Binding of the Dopamine D3Receptor-Preferring Ligand [11C]-(+)-Propyl-Hexahydro-Naphtho-Oxazin in Methamphetamine Polydrug Users: A Positron Emission Tomography Study

Abstract: Positron emission tomography (PET) findings suggesting lower D2-type dopamine receptors and dopamine concentration in brains of stimulant users have prompted speculation that increasing dopamine signaling might help in drug-treatment. However, this strategy needs to consider the possibility, based on animal and postmortem human data, that dopaminergic activity at the related D3 receptor might, in contrast, be elevated, and thereby contribute to drug-taking behavior. We tested the hypothesis that D3 receptor bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
157
4
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 160 publications
(190 citation statements)
references
References 49 publications
(76 reference statements)
28
157
4
1
Order By: Relevance
“…consistent with predominant D2R-mediated signal associated with [ 11 C]PHNO binding potential and pharmacological studies suggesting that the descending limb of the quinpirole-elicited yawning dose-response curve is D2R-mediated (Collins et al, 2005(Collins et al, , 2007. Recent PET studies of chronic cocaine (Payer et al, 2014) and polydrug MA (Boileau et al, 2012) users reported that both drugs were associated with elevated levels of D3R availability in the substantia nigra. Furthermore, the use of cocaine and MA has previously been shown to be associated with decreased D2-like receptor availability (Volkow et al, 1990(Volkow et al, , 2001Nader et al, 2006;Payer et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…consistent with predominant D2R-mediated signal associated with [ 11 C]PHNO binding potential and pharmacological studies suggesting that the descending limb of the quinpirole-elicited yawning dose-response curve is D2R-mediated (Collins et al, 2005(Collins et al, , 2007. Recent PET studies of chronic cocaine (Payer et al, 2014) and polydrug MA (Boileau et al, 2012) users reported that both drugs were associated with elevated levels of D3R availability in the substantia nigra. Furthermore, the use of cocaine and MA has previously been shown to be associated with decreased D2-like receptor availability (Volkow et al, 1990(Volkow et al, , 2001Nader et al, 2006;Payer et al, 2014).…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, the highest uptake and binding potentials were in the caudate nucleus, putamen, and ventral striatum. Previous studies in humans found a similar pattern of distribution of PHNO binding, with highest binding potentials in the putamen, globus pallidus, and substantia nigra (Searle et al, 2010;Boileau et al, 2012;Gallezot et al, 2014). Tziortzi and colleagues (2011) …”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Moreover, pharmacological treatment with nonselective D2/D3 receptor agonists may have untoward effects by augmenting D3 vs D2 receptor signaling. Notably, stimulant users show greater D3 receptor availability in the limbic striatum compared with healthy control subjects (Boileau et al, 2012). Therefore, nonpharmacologic approaches, such as structured exercise training, that augment dopaminergic signaling in physiologically relevant ways may be useful in treating those with substance use disorders.…”
Section: Discussionmentioning
confidence: 99%